Characterization Method of Tight Sandstone Reservoir Heterogeneity and Tight Gas Accumulation Mechanism, Jurassic Formation, Sichuan Basin, China. (20th July 2022) - Jiang, Lin; Zhao, Wen; Zhang, Benjian; Zheng, Chao; Hong, Feng; Hao, Jiaqing
Abstract : Although significant progress has been made in tight gas exploration and development, there is still a limited understanding of the gas accumulation mechanism in tight formation. The description of heterogeneity in the tight reservoir is still an obstacle during tight gas exploration. In this work, we will develop a 3D gas accumulation facility that can reflect the high temperature and pressure under the geological condition to simulate the gas accumulation process in the tight formation of the Jurassic Formation, Sichuan Basin. Both the physical experiment simulation and numerical simulation methods will be combined to reveal the mechanism of gas accumulation. The results show that (1) the permeability ratio can characterize the heterogeneity of tight reservoirs. Based on this parameter, petroleum geologists can understand the interlayer heterogeneity during fluvial deposition and predict the sweet spots of tight gas; (2) the permeability ratio relationship between hydrocarbon accumulation of the tight sandstone reservoir mainly manifests as long as there is the existence of the differential permeability and there will be differences in natural gas migration dynamics, so that the natural gas accumulates in pores and depends on the extent of source rock; and (3) although the difference between capillary force curves is at the core of the influence of the permeability ratio on the gas-bearing capacity of the "sweet spot" sand body, the permeability ratio is a parameter of practical engineering significance. This work adds new methods to tight gas formation heterogeneity characterization and sheds light on the mechanisms of hydrocarbon accumulation in tight formation.